2018
DOI: 10.3390/molecules23092295
|View full text |Cite
|
Sign up to set email alerts
|

Molybdenum Trioxide: Efficient Nanosorbent for Removal of Methylene Blue Dye from Aqueous Solutions

Abstract: Nano Molybdenum trioxide (α-MoO3) was synthesized in an easy and efficient approach. The removal of methylene blue (MB) in aqueous solutions was studied using this material. The effects of various experimental parameters, for example contact time, pH, temperature and initial MB concentration on removal capacity were explored. The removal of MB was significantly affected by pH and temperature and higher values resulted in increase of removal capacity of MB. The removal efficiency of Methylene blue was 100% at p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 87 publications
2
29
0
Order By: Relevance
“…As a matter of fact, the data show a decrease in dye removal from 99% to 73% with a decrease in removal capacity from 15,900 to 11,608mg/g. The maximum adsorption capacity obtained after four cycles of use (11,608 mg/g) was higher than that obtained by several nanosorbents [ 30 , 87 , 88 , 89 , 90 , 91 , 92 ]. The high level of removal efficiency showed that the adsorbent regeneration by way of calcination under atmospheric air at a temperature of 400 °C was extremely efficient and indicative of outstanding recycling capability.…”
Section: Resultsmentioning
confidence: 61%
See 3 more Smart Citations
“…As a matter of fact, the data show a decrease in dye removal from 99% to 73% with a decrease in removal capacity from 15,900 to 11,608mg/g. The maximum adsorption capacity obtained after four cycles of use (11,608 mg/g) was higher than that obtained by several nanosorbents [ 30 , 87 , 88 , 89 , 90 , 91 , 92 ]. The high level of removal efficiency showed that the adsorbent regeneration by way of calcination under atmospheric air at a temperature of 400 °C was extremely efficient and indicative of outstanding recycling capability.…”
Section: Resultsmentioning
confidence: 61%
“…Regeneration techniques suggested in the literature include chemical extraction, thermal treatment, supercritical regeneration, microwave irradiation, bio-regeneration, etc. [ 25 , 88 , 93 , 94 , 95 ]. The thermal regeneration, which has been applied for molybdenum oxide nanosorbent, was described in our previously published work [ 88 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Temperature is another parameter of prime importance that has a great impact on dye removal [45]. The process of removing the MB dye was investigated from 20 to 70 • C, as can be seen in Figure 4.…”
Section: Temperature Effectmentioning
confidence: 99%